In Everything God Works for Good: A Study of Romans 8:28-29 - Mambu, Amelius T (JIU (Jurnal Ilmiah Unklab); Volume 3 No. 1, 2000 JIU UNKLAB, 2000)
Romans 8:28-29 presents three possibilities in interpreting the subject of the phrase “in everything God works for good with those who love God,” namely, the Holy Spirit, all things, or God Himself. The translation of the Holy Spirit as the subject of the phrase is found in NEB–“and in everything, as we know, he co-operates for good with those who love God.” The subsequent verses do not support this translation since Jesus was never called as the son of the Holy Spirit. Next, grammatically “all things” could become the subject of the phrase–“and we know that all things work together for good to them that love God.” Paul, however, shows that God Alone who is able to cause “all things” work for good to all his believers– “and we know that in all things God works for the good of those who love him.” RSV